A systematic review of menstrual hygiene management (MHM) during humanitarian crises and/or emergencies in low- and middle-income countries - Patel, Kripalini; Panda, Nishisipa; Sahoo, Krushna Chandra; Saxena, Shipra; Chouhan, Narendra Singh; Singh, Pratibha; Ghosh, Upasona; Panda, Bhuputra (Frontiers in Public Health, 2022)
Background: Poor menstrual hygiene management (MHM) is linked to adverse health, and quality of life, particularly during emergencies. Although in recent times increased emphasis is being laid upon MHM during humanitarian crises – pandemics, disasters and conflicts, the essential components of complete MHM during an emergency are not clearly spelt out. We conducted a systematic review to examine, analyse and describe the existing evidence related to the challenges experienced by women and girls in practicing MHM during humanitarian crises and / or public health emergencies. Methods: We followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses 2020 guidelines and registered in PROSPERO (CRD42022328636). We searched online repositories: PubMed, Embase, and PsycINFO for articles published between January 2000 and April 2022. For presenting key findings, we used the descriptive statistics and thematic analysis approach Results: We identified a total of 1078 published articles, out of which 78 were selected for a full-text review, and finally 22 articles were included. The pooled prevalence of lack of access to sanitary pads during humanitarian crises was 34 percent (95 percent CI 0.24–0.45). The prevalence of sanitary pad disposal ranged from 11 to 85 per cent, with a pooled prevalence of 54 per cent (95 per cent CI 0.21–86). Qualitative analyses projected three themes that emerged on MHM during humanitarian crises 1) Availability and affordability of menstrual products, and accessibility to water, sanitation and health (WASH) services, 2) Availability of support system and coping with ‘period poverty’, and 3) Gender dimensions of menstrual hygiene management. Most studies reported non-availability of MHM products and WASH services during emergencies. Existence of barriers at systemic and personal level posed challenges in practicing menstrual hygiene. Privacy was identified as a common barrier, as emergency shelters were reportedly not women-friendly. Conclusion: Availability of limited evidence on the subject is suggestive of the need to invest resources for strengthening primary research in LMICs and more specifically during emergencies. Context-specific state level policies on MHM during emergencies would help to guide district and sub-district managers in strengthening systems and address barriers for the provision of MHM services during emergencies.